Improving the Seventh Grade Students’ Reading Comprehension Achievement by Using Mind Mapping Technique at Itisam Wittaya Foundation School - Lahab, Rachnok; Fitriyah, Siti Masrifatul; Sukmaantara, I Putu (EFL Education Journal, 2022)
This research focused on Improving the Seventh Grade Students’ Reading Comprehension Achievement by Using Mind Mapping Technique at Itisam Wittaya Foundation School this research aims to fill in the gap and focus on investigating the use of mind mapping technique to improve students’ reading comprehension achievement on the seventh grade students of Itisam Wittaya Foundation School.